1981
DOI: 10.1002/jcp.1041090220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroliberin (TRH) on cell proliferation and prolactin secretion by GH3/B6 rat pituitary cells: A comparison between serum‐free and serum‐supplemented media

Abstract: Numerous studies have shown that prolactin (PRL) production by GH3 cells grown in serum supplemented media is regulated by several hormones including thyroliberin (TRH). The recent availability of hormonally defined, serum-free media for the growth of GH3 cells has made it possible to determine the effect of TRH in absence of other prolactin regulating hormones. Here we demonstrate that transfer of GH3/B6 cells from serum-supplemented medium to serum-free media results in several important changes: (1) altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As for the GH cell line, it was shown that EGF stimulated prolactin (PRL) production and inhibited growth hormone (GH) production accompanied by the inhibitory action on cellular growth (Johnson et al, 1980;Schonbrunn et al, 1980). Similar effects on cell proliferation and hormone production have also been reported with thyrotropin-releasing hormone (TRH), which regulates the GH cell line (Schonbrunn et al, 1980;Brunet et al, 1981). TRH stimulates the PRL production, which inhibits the GH production, and also suppresses the rate of proliferation of GH3 cells.…”
mentioning
confidence: 84%
“…As for the GH cell line, it was shown that EGF stimulated prolactin (PRL) production and inhibited growth hormone (GH) production accompanied by the inhibitory action on cellular growth (Johnson et al, 1980;Schonbrunn et al, 1980). Similar effects on cell proliferation and hormone production have also been reported with thyrotropin-releasing hormone (TRH), which regulates the GH cell line (Schonbrunn et al, 1980;Brunet et al, 1981). TRH stimulates the PRL production, which inhibits the GH production, and also suppresses the rate of proliferation of GH3 cells.…”
mentioning
confidence: 84%
“…TRH regulates the synthesis and secretion of TSH and PRL by thyrotroph and lactotroph cells, respectively (30). In addition, TRH regulates proliferation of specific pituitary cells (31,32) and has been implicated in the formation of pituitary adenomas (33). TRH binds and activates two G protein-coupled receptors, TRHR1 and TRHR2 (34), which transduce signals predominantly via the PKC and mitogen-activated protein kinase (MAPK) pathways (35)(36)(37).…”
mentioning
confidence: 99%
“…Clausen et al (1978) reported that, using microfluorometric ana¬ lysis, TRH decreased the number of cells in the S phase by about 40% while increasing the number of cells in Gi. It has also been reported that TRH showed a slight suppression of the growth of subclones of GH3 cell lines in the medium supple¬ mented with serum (Schonbrunn et al 1980;Brunet et al 1981). Our results are compatible with these findings.…”
Section: Discussionmentioning
confidence: 95%